Updating the USDA national breastfeeding campaign workshop summary - Updating the USDA National Breatfeeding Campaign: Loving Support Makes Breatfeeding Work (2011 : Washington, D.C.); Whitacre, Paula; Moats, Sheila A.; Institute of Medicine (U.S.); Institute of Medicine (U.S.). Food and Nutrition Board; ebrary, Inc. (Washington, D.C. : National Academies Press, 2011)
Support for breastfeeding has been a priority of the WIC program since its inception in the 1970s. The Loving Support Makes Breastfeeding Work campaign, which the U.S. Department of Agriculture's (USDA) Food and Nutrition Services launched in 1997, emphasizes key components needed for a breastfeeding mother to be successful. More than a decade after the campaign began, USDA wants to update it, taking into account changes in the WIC program, participants, and technology. On April 26, 2011, the IOM hosted a workshop to bring together experts to discuss what has changed since Loving Support began, lessons learned from other public health campaigns, and suggestions for where to take the campaign in the future--
Opening session -- What has changed? -- Lessons learned from other social marketing and breastfeeding campaigns -- Where does the breastfeeding campaign go from here? -- Responses and concluding remarks.
"Food and Nutrition Board."
Includes bibliographical references.
Electronic reproduction.
Keywords: Breastfeeding -- United States -- Congresses; Breastfeeding -- Economic aspects -- United States -- Congresses; Breastfeeding promotion -- United States -- Congresses; Poor women -- Education -- United States -- Congresses; Infants -- Nutrition -- Congresses; Health promotion -- United States -- Congresses; Nuclear facilities -- United States -- Congresses; Electronic books